Development and study of novel frequency-hopped multiple-access receiver - Chaurasia Nisha (2015)
Frequency Hopping Spread Spectrum (FHSS) systems refer to the signal broadcast over seemingly random series of frequencies. These systems have been popular in commercial and military applications as eavesdroppers hear unintelligible blips and only a few bits are affected due to the jamming on one frequency. This dissertation focuses on the performance of Binary Frequency-Shift Keying (BFSK), Fast Frequency-Hopped Spread Spectrum (FFHSS) system, Fast Frequency-Hopped/ Binary Frequency-Shift Keying (FFH/BFSK) linear combining receiver and Frequency-Hopped Multiple Access (FHMA) system over various fading channels such as Additive White Gaussian Noise (A WGN), Rayleigh fading channel and Rician fading channel. The Bit-Error Rate (BER) performance of the systems over different fading channels is obtained via simulation and is compared which shows that for a wide range of signal-to-noise ratio, the performance of the system is affected by different factors such as number of users, modulation order, fading models, number of hops per bit, etc.